Effectiveness of Box Container Assistance for Indigenous Papuan MSMEs in Sorong City - Banggu, Masni; Ula, Siti Nurul Nikmatul; Wanma, Januari Christy; Rais, Lukman (Universitas Muhammadiyah Tangerang, 2025)
MSME assistance programs generally focus on capital and entrepreneurship training. However, it is still limited to the evaluation of assistance in the form of business facilities. This study aims to evaluate the effectiveness of the box container assistance program in encouraging the increase of small and medium enterprises of indigenous Papuans. Contributing to the development of knowledge in the field of MSME empowerment policies, especially in the context of support for business actors from indigenous Papuans. Using a mixed method approach, between quantitative and qualitative methods used together in a research activity by collecting data through interviews, observations, surveys of 45 indigenous Papuan MSME actors who received box container assistance in Sorong City. The results of the study showed that with the existence of this box container assistance program, it became business capital for indigenous Papuans in starting their businesses, creating jobs for women (housewives), as much as 53.33% increased income and could adjust to the location of sales for the community. However, there are still challenges due to the lack of supervision in the field in the use of this business capital assistance facility. However, this assistance program can be a model/sustainable assistance program for indigenous Papuans in developing their small and medium enterprises by considering several requirements and criteria. Program bantuan UMKM secara umum banyak menyoroti tentang permodalan dan pelatihan kewirausahaan. Namun, masih terbatas pada evaluasi bantuan berupa sarana usaha. Penelitian ini bertujuan untuk mengevaluasi efektivitas program bantuan box container dalam mendorong peningkatan usaha kecil menengah masyarakat asli Papua. Memberikan kontribusi terhadap pengembangan pengetahuan dalam bidang kebijakan pemberdayaan UMKM, khususnya dalam konteks dukungan terhadap pelaku usaha dari kalangan masyarakat asli Papua. Menggunakan pendekatan metode campuran, antara metode kuantitatif dan metode kualitatif yang digunakan secara bersama-sama dalam suatu kegiatan penelitian dengan mengumpulkan data melalui wawancara, observasi, survei terhadap 45 orang pelaku UMKM masyarakat asli Papua penerima bantuan box container di Kota Sorong. Hasil penelitian menunjukkan bahwa dengan adanya program bantuan box container ini, menjadi modal usaha bagi masyarakat asli Papua dalam memulai usahanya, menciptakan lapangan kerja bagi perempuan (ibu rumah tangga), sebanyak 53,33% adanya peningkatan pendapatan dan dapat menyesuaikan dengan lokasi berjualan bagi masyarakat. Namun, masih terdapat tantangan karena kurangya pengawasan dilapangan dalam penggunaan sarana bantuan modal usaha ini. Tetapi, program bantuan ini dapat menjadi model/program bantuan berkelanjutan bagi masyarakat asli Papua dalam mengembangkan usaha kecil menengahnya dengan mempertimbangkan beberapa syarat dan kriteria.